Um estudo sobre ISTs e as relações afetivo-sexuais em universitários - Moura, Ana Beatriz de (Universidade Federal de São Carlos, 2021)
According to the World Health Organization (2018), more than 1 million Sexually Transmitted Infections (STIs) are acquired every day in the world. Each year, 376 million new curable infections are estimated: trichomoniasis (156 million), chlamydia (127 million), gonorrhea (87 million) and syphilis (6 million). Approximately 291 million women are infected with the HPV virus. Considering these risks, the present study investigated the experience of STI contamination and their impact on the affective-sexual relationships of university students. For this purpose, a semi-structured interview was done to verify how health care was provided, how the person deals with confidentiality or not, regarding the condition and to verify the weakening and/or strengthening aspects of affective-sexual relationships in the context of STI, if any. The interviews were recorded, transcribed and analyzed using the content thematic analysis technique. 06 university students (01 woman, 05 men) participated, with an average age of 23.5 years, presenting the following STIs: candidiasis, gonorrhea, genital herpes, HPV, syphilis and trichomoniasis. The interviews’ analysis produced 4 categories: 1. Protection logics; 2. Health care focused on STI; 3. Reception and support network; 4. Stigma and Taboo. The results showed a weak protection logic, marked by the idea of ​​non-vulnerability, obtaining a variation in the search for health care and the weakness in the technical approach by the professionals responsible for care. In addition, autonomy and freedom to exercise sexual interactions can be observed, but also the preservation of stigmas and taboos when there is a need to deal with the possible consequences of sexuality, such as STIs.
A study about STIs and Intimate Relations Among College Students
Keywords: Universitários; IST; Relações afetivo-sexuais; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::RELACOES INTERPESSOAIS; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL